Computational evaluation of frictional force changes in three-point and three-bracket bending models / S. A. H. A. Seman ... [et al.] - Seman, S. A. H. A.; Razali, M. F.; Mahmud, A. S.; Hassan, M. H. (Universiti Teknologi MARA, 2021)
NiTi arch wires are commonly used at the initial stage of orthodontic treatment, due to their superelastic and biocompatibility properties. Numerous bending models have been considered to anticipate the mechanical responses of the superelastic NiTi wire in the oral environment. It is known that the magnitude of bending force exerted by the NiTi wire is relatively influenced by the magnitude of friction generated at the wiresupport interfaces. These data on the variability of friction magnitude for various bending models, however, are very limited in the literature. This study investigated the magnitude of frictional force generated in different bending models through the numerical method. The frictional force in a three-point and a three-bracket model was quantified from the force difference, measured when the wire was deflected in friction and frictionless conditions. Overall, the frictional force magnitude gradually increased as the wire further pressing the support surface at higher deflection. The highest frictional force was recorded when the bracket support was considered, with values of 2.01 N during loading and 1.61 N during unloading. These loading and unloading frictional forces were significantly reduced to 0.25 N as soon as the point support was considered. The high frictional force generated in the bracket model transformed the constant force-deflection trend of superelastic NiTi wire into a gradient force.